Is Spiritual Leadership Powerful for Strengthening Organizational Commitment? - Mohammad Syafiudin; Fendy Suhariadi; Praptini Yulianti; Tatik Suryani (Universitas Hayam Wuruk Perbanas, 2022)
Spiritual leadership has recently become a hot topic of discussion because it is related to organizational commitment. The success of organizational commitment is strongly supported by the presence of meaning, membership and empowerment. This research was conducted at the State Owned Enterprise, PT. Pelindo (Region III) involving 160 respondents from various divisions who met the requirements. Structural equation modeling was applied using AMOS to explore the proposed relationships. The results of this study indicate that spiritual leadership has a direct effect on meaning, membership, and empowerment of the leaders. Meanwhile, meaning, membership, and empowerment of the leaders have a significant positive effect on organizational commitment. In addition, the results also show that meaning, membership, and empowerment of the leaders mediate the effect of spiritual leadership on organizational commitment. This research provides information to the leaders of PT. Pelindo (Region III) in order to be able to make effective decisions about why and under what circumstances leaders / supervisors can have high organizational commitment.